Strengthening Financial Stability through Cash Control Training for MSMEs Managers in the Automotive Service Sector - Nurjanna Nurjanna; Asrianti A. Latif; Suharti Sirajuddin; Hariany Idris; Nurafni Oktaviyah (PT. Global Research Collaboration, 2025)
Cash control is a crucial aspect of financial management for micro, small, and medium enterprises (MSMEs), which often face challenges in maintaining liquidity stability and operational efficiency. This study aims to analyze the implementation of cash control systems in MSMEs and their impact on business sustainability. The method used is qualitative descriptive with a case study approach conducted on several MSMEs in the trade and service sectors. The results show that most MSMEs have not adequately implemented cash control systems, particularly in daily transaction recording, segregation of financial functions, and the use of cash budgets. As a result, MSMEs are at risk of experiencing operational fund shortages and difficulties in making financial decisions. This study recommends the need for education and assistance for MSME actors in implementing simple yet effective cash control systems to enhance business sustainability and competitiveness.